The wide window - Snicket, Lemony; Helquist, Brett (New York : HarperCollins Publishers, 2000)
Catastrophes and misfortune continue to plague the Baudelaire orphans after being sent to live with fearful Aunt Josephine, who offers little protection against Count Olaf's treachery.
Keywords: Orphans -- Juvenile fiction; Siblings -- Juvenile fiction; Humorous stories